Analysis of Thin Slice Computed Tomography Features of Coronavirus Disease 2019 Related Vascular Abnormalities - Xingpeng LI; Hui YUAN; Changyue DU; Xiaoyan LIU; Ling LI; Mengke LIU; Yimeng ZHANG; Yan ZHANG; Qi HAO; Shuhong DUAN; Rengui WANG (CT Lilun yu yingyong yanjiu, 2023)
Objective: This study aimed to explore the clinical value of thin slice computed tomography (CT) plain scan in the analysis of CT features of vascular abnormalities associated with coronavirus disease 2019 (COVID-19). Materials and methods: A total of 73 patients with COVID-19 confirmed by the Department of Infection of Beijing Shijitan Hospital from December 5, 2022 to December 17, 2022, were included in the study. Chest thin CT plain scan images showed that the lesions involved blood vessels were retrospectively collected. All patients had complete chest thin CT plain scan and relatively complete clinical data. According to age (>60 and ≤60 years), the patients were divided into the young and elderly groups. The chest imaging manifestations of all patients were observed and statistically analyzed between different age groups. Results: Among the 73 patients with COVID-19, the imaging indexes with statistical significance between the young and elderly groups were as follows: the distribution of the lesion around the central blood vessel, size of the lesion (10~30 mm), size of the lesion (>30 mm), percentage of the lesion to the volume of the lung lobe (≤30), percentage of the lesion to the volume of the lung lobe (>50) (white lung), shape of the lesion was large, the dominant type of the lesion was acinar, vascular distortion, vascular margin fuzzy, and tree-bud sign thick fiber rope. Conclusion: (1) Chest thin-slice CT plain scan can identify the number, location, involved location, scope, vascular abnormality, and pathological type of COVID-19-related vascular abnormality, which has certain significance for the qualitative and differential diagnosis of COVID-19 vascular abnormality. (2) The chest thin CT plain scan is of great significance for finding elderly patients with COVID-19 involving blood vessels. (3) COVID-19-related "blood vessel thickening" can be caused by either the diameter of the blood vessel itself or the inflammatory edema of the perivascular interstitium.